2020
DOI: 10.12659/ajcr.924446
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Rechallenge After Cardiotoxicity

Abstract: Patient: Male, 66-year-old Final Diagnosis: Colon adenocarcinoma • ventricular arrhythmia Symptoms: Cardiac arrest • syncope Medication: — Clinical Procedure: Cardiac catheterization • Cardiac Electronic Implantable Device (CEID) Specialty: Cardiology • General and Internal Medicine • Oncology Objective: Unusual clinical course Background: 5-Fluorouracil (5-FU) is a widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
1
7
0
5
Order By: Relevance
“…In the present study, 5FU treated rats showed a signi cant elevation in the activity of serum CK-MB, LDH, ALT, AST levels indicating 5FU induced myocardial necrotic damage and the leakiness of the plasma membrane. This is in accordance with Lamberti et al 1 ; Desai et al 22 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 5FU treated rats showed a signi cant elevation in the activity of serum CK-MB, LDH, ALT, AST levels indicating 5FU induced myocardial necrotic damage and the leakiness of the plasma membrane. This is in accordance with Lamberti et al 1 ; Desai et al 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Early studies have identified the effects of 5-FU on the coronary arteries, and knowledge about its cardiovascular toxicity and adverse effects on the coronary arteries has improved with advances in treatments. The incidence of cardiovascular toxicity caused by 5-FU ranges from 2% to 18% ( 51 , 52 ). Another retrospective analysis summarized the mortality risk from the cardiovascular adverse effects of 5-FU.…”
Section: Chemotherapeutic Drugsmentioning
confidence: 99%
“…Various drugs can also induce CAS, including psychostimulants, vasoconstricting agents, and immunosuppressive medications, such as calcineurin inhibitors and fluorouracil. 13,23 Myocardial bridging is an anatomical variant in which the epicardial coronary arteries pass through cardiac muscle layers and become compressed during systole. Montone et al found that patients with this condition are more likely to have a positive acetylcholine test and it may be a predictor of MINOCA.…”
Section: Risk Factors For Coronary Spasmmentioning
confidence: 99%